An Overview of Deep Learning Based Methods for Unsupervised and Semi-Supervised Anomaly Detection in Videos - B. Ravi Kiran; Dilip Mathew Thomas; Ranjith Parakkal (Journal of Imaging, 2018)
Videos represent the primary source of information for surveillance applications. Video material is often available in large quantities but in most cases it contains little or no annotation for supervised learning. This article reviews the state-of-the-art deep learning based methods for video anomaly detection and categorizes them based on the type of model and criteria of detection. We also perform simple studies to understand the different approaches and provide the criteria of evaluation for spatio-temporal anomaly detection.